Pengaruh Peran Orang Tua Dan Pelatih Terhadap Pembentukan Karakter Atlet Usia 15 Tahun - Da'i, Mohamad; Apriyanto, Rohmad; S, Adi; Aliriad, Hilmy (Universitas Nusantara PGRI Kediri, 2023)
This study aims to find out the influence of the role of parents and coaches on the character of the 15-year-old athlete PASI Bojonegoro. This research is correlational research using a quantitative approach. Data collection techniques using questionnaires. The sample of this study consisted of 12 respondents from 15 years old PASI Bojonegoro athletes using purposive sampling techniques. The reliability and validity of the instruments used in this study have been checked, and consulted with experts. Data analysis techniques based on double regression. Based on the results of the analysis of the t test obtained variable significance values of the role of parent p<0,05 and trainer p <0,05. It shows that partly the role of parents and coaches influenced the character of athletes PASI Bojonegoro aged 15. Using the analysis test F, resulted in a degree of significance p less than 0.05, while the Rpersegi value = 0.621 means 78.8% of characteristics athlete PASI district Bojoneegoro are influenced by the roles of the parent and coach. Thus it can be concluded that the role of parent and coach simultaneously has an influence on the character of the athlete PASI Bojonegoro. Therefore, in giving character education to athletes both inside and outside the field, there is a need for encouragement from outside, both from parents and coaches.